Flagellin is a strong vaginal adjuvant of a therapeutic vaccine for genital cancer. (1st February 2016) - Lee, Shee Eun; Hong, Seol Hee; Verma, Vivek; Lee, Youn Suhk; Duong, Tra-My Nu; Jeong, Kwangjoon; Uthaman, Saji; Sung, Young Chul; Lee, Jae-Tae; Park, In-Kyu; Min, Jung-Joon; Rhee, Joon Haeng
ABSTRACT: Cervical cancer is a high-incidence female cancer most commonly caused by human papilloma virus (HPV) infection of the genital mucosa. Immunotherapy targeting HPV-derived tumor antigens (TAs) has been widely studied in animal models and in patients. Because the female genital tract is a portal for the entry of HPV and a highly compartmentalized system, the development of topical vaginal immunotherapy in an orthotopic cancer model would provide an ideal therapeutic. Thus, we examined whether flagellin, a potent mucosal immunomodulator, could be used as an adjuvant for a topical therapeutic vaccine for female genital cancer. Intravaginal (IVAG) co-administration of the E6/E7 peptides with flagellin resulted in tumor suppression and long-term survival of tumor-bearing mice. In contrast to IVAG vaccination, intranasal (IN) or subcutaneous (SC) immunization did not induce significant tumor suppression in the same model. The vaginal adjuvant effect of the flagellin was completely abolished in Toll-like receptor-5 (TLR5) knock-out mice. IVAG immunization with the E6/E7 peptides plus flagellin induced the accumulation of CD4 + and CD8 + cells and the expression of T cell activation-related genes in the draining genital lymph nodes (gLNs). The co-administered flagellin elicited antigen-specific IFNγ production in the gLNs and spleen. The intravaginally administered flagellin was found in association with CD11c + cells in the gLNs. Moreover, after immunization with a flagellin and the E6/E7 peptides, the TLR5 expression in gLN cells was significantly upregulated. These results suggest that flagellin serves as a potent vaginal adjuvant for a therapeutic peptide cancer vaccine through the activation of TLR5 signaling.